Analysis of Newcastle disease virus prevalence in wild birds reveals interhost transmission of genotype VI strains - Tingting Zeng; Liji Xie; Zhixun Xie; Jun Hua; Jiaoling Huang; Zhiqin Xie; Yanfang Zhang; Minxiu Zhang; Sisi Luo; Meng Li; Can Wang; Lijun Wan; et al. (Microbiology Spectrum)
ABSTRACT Newcastle disease virus (NDV) can infect more than 200 species of birds, and most reports have focused on poultry. The pathogenic ecology of NDV in wild birds remains largely unknown. Thus, an investigation of NDV in domestic wild birds and pigeons was conducted. Thirty-nine NDV strains were characterized from 3,549 oropharyngeal and cloacal swab samples collected from 2016 to 2019 in Guangxi, China. Among them, 3 NDV strains belonged to class I genotype 1.1.2, and 36 strains belonged to class II, including 6 strains belonging to genotype I, 1 strain belonging to genotype II, 4 strains belonging to genotype VI.2.1.1.2.1, 23 strains belonging to genotype VI.2.1.1.2.2, and 2 strains belonging to genotype XII. Phylogenetic analysis revealed that genotype VI NDVs circulate among multiple species of resident wild birds and may spread back to pigeons. In addition, resident wild birds are important for short-distance NDVs transmission. The prevalence of NDVs in wild birds indicates that more restrictive biosecurity measures and ongoing epidemiological investigations are needed.IMPORTANCESurveillance of Newcastle disease viruses (NDVs) has been conducted primarily in poultry, but their prevalence in wild birds remains largely unknown. Increasing our understanding of the ecology and evolution of NDVs in different species of birds will help us develop better prevention and control strategies. In this study, large-scale epidemiological sampling of resident wild birds in Guangxi from 2016 to 2019 was performed. The results demonstrated that different genotypes, especially genotype VI NDVs, circulated among resident wild birds. Our findings highlight the potential threat to the pigeon industry and public health.